2022
DOI: 10.1182/blood.2021013568
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome landscape of adult T-cell leukemia/lymphoma

Abstract: Adult T-cell leukemia/lymphoma (ATL) is an aggressive neoplasm immunophenotypically resembling regulatory T cells, associated with human T-cell leukemia virus type-1. Here we performed whole-genome sequencing (WGS) of 150 ATL cases to reveal the overarching landscape of genetic alterations in ATL. We discovered frequent (33%) loss-of-function alterations preferentially targeting the CIC long isoform, which were overlooked by previous exome-centric studies of various cancer types. Long but not short isoform-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 47 publications
3
35
0
Order By: Relevance
“…“Chronic lymphoproliferative disorder of NK cells” in WHO-HAEM4R has been renamed NK-large granular lymphocytic leukaemia (NK-LGLL) , given recent evidence that this is a monoclonal or oligoclonal expansion of NK cells that has many similarities with T-LGLL. Genetic analyses of adult T-cell leukaemia/lymphoma (ATLL) have revealed novel events that highlight the importance of immune evasion including CTLA4 :: CD28 and ICOS :: CD28 fusions, REL C-terminal truncations [ 215 , 216 ], recurrent alterations in HLA-A and HLA-B and structural variations disrupting the 3′-untranslated region of CD274 ( PD-L1) [ 217 ]. Furthermore, the frequency and pattern of somatic alterations appear to be correlated with clinical behavior.…”
Section: B-cell Lymphoid Proliferations and Lymphomasmentioning
confidence: 99%
“…“Chronic lymphoproliferative disorder of NK cells” in WHO-HAEM4R has been renamed NK-large granular lymphocytic leukaemia (NK-LGLL) , given recent evidence that this is a monoclonal or oligoclonal expansion of NK cells that has many similarities with T-LGLL. Genetic analyses of adult T-cell leukaemia/lymphoma (ATLL) have revealed novel events that highlight the importance of immune evasion including CTLA4 :: CD28 and ICOS :: CD28 fusions, REL C-terminal truncations [ 215 , 216 ], recurrent alterations in HLA-A and HLA-B and structural variations disrupting the 3′-untranslated region of CD274 ( PD-L1) [ 217 ]. Furthermore, the frequency and pattern of somatic alterations appear to be correlated with clinical behavior.…”
Section: B-cell Lymphoid Proliferations and Lymphomasmentioning
confidence: 99%
“…Adult T cell leukemia/lymphoma (ATL) is a malignancy of peripheral T lymphocytes provoked by human T cell leukemia virus type 1 infection (HTLV-1). This leukemia is extremely resistant to treatment, and it is estimated that at least 5-10 million patients are infected with HTLV-1, the first human oncogenic retrovirus detected [142].…”
Section: Tnts and T Cell Acute Lymphoblastic Leukaemia (T-all)mentioning
confidence: 99%
“…Previous studies found that CD58 is a glycoprotein expressed on the surface of B cells, T cells, monocytes, granulocytes and thymic epithelial cells, an important member of the immune superprotein family, and has a role in promoting cell adhesion [19]. We found that the main studies of CD58 focused mainly on hematological tumors [23][24][25]27], skin diseases [35], where CD58 plays a rather important role through different mechanisms. There are also a few other malignant tumors, such as cervical cancer[28],…”
Section: Discussionmentioning
confidence: 95%
“…Aggressive ATLL is refractory to conventional chemotherapy and has a poor prognosis. The genetic pro le of ATLL shows frequent alterations in genes associated with immune surveillance, including major histocompatibility complex (MHC) class I, CD58 antigen, programmed cell death ligand 1 (PDL1), HLA-A/B, FAS [23,24]. Downregulation of CD58 allows immune escape occur [25].…”
Section: Introductionmentioning
confidence: 99%